Small industry in Peru - Mechthild Minkner (Intereconomics, 1975)
Peru's small industry has so far been a stagnant marginalized sector of industry. It does not yet form part of the modern structure of medium-sized and large enterprises as a complementary or even as a competitive element. But now the Peruvian Government announced officially that legislation will shortly be passed for the promotion of small industry.
Keywords: 330; Industrialization